Determination of the Objective Reason Condition in the Conclusion and Renewal of Fixed Term Employment Contracts - ÜNAL ADINIR, CANAN (ISTANBUL UNIV, FAC LAW, 2021)
An employment contract may be executed for a fixed or indefinite term. An indefinite-term employment contract is the rule of thumb, whereas a fixed-term contract is an exception. According to Article 11 of the Employment Code No 4857, a fixed-term contract may be signed when it is based on an objective reason, such as fixed-term work, the completion of a certain job, or the emergence of a relevant fact. There is no similar provision in other employment codes, which is why concluding a fixed-term employment contract with a worker covered by the Employment Code is more difficult than terminating workers excluded from the said code. This strict structure to conclude a fixed-term employment contract of the Employment Code has been criticized by the doctrine. According to Article 11, paragraphs 2 and 3, of the Employment Code and Article 430 of the Obligation Code No. 6098, to renew a fixed-term employment contract with all workers, an objective reason is required. This article explains what objective reason means and if such a condition is suitable and evaluates the debates in the doctrine and legal studies regarding the objective reason condition in the conclusion of fixed-term employment contracts, regulated in Article 11 of the Employment Code. Further, the author discusses whether an exception should be introduced into the objective cause condition. This article next examines the objective reason condition for the renewal of fixed-term employment contracts. In this framework, in addition to the objective reason condition, the application of a time limit and a number limit will be evaluated to prevent abuse in the renewal of employment contracts by using successive fixed-term employment agreements.
Keywords: Fixed-term employment contract; Objective reason; Employment Code No. 4857; Obligation Code No. 6098; Maritime Employment Code; Press Employment Code; Successive employment contract; Renewal; Maximum total duration; Maximum number of renewals